Symptoms of depression and anxiety among elite high school student-athletes in Sweden during the COVID-19 pandemic: A repeated cross-sectional study - Andersson, M. J.; Kenttä, G.; Moesch, K.; Borg, E.; Claesdotter-Knutsson, E.; Håkansson, A. (Journal of Sports Sciences, 2023)
The COVID-19 pandemic precipitated numerous changes in daily life, including the cancellation and restriction of sports globally. Because sports participation contributes positively to the development of student-athletes, restricting these activities may have led to long-term mental health changes in this population. Using a repeated cross-sectional study design, we measured rates of depression using the Patient Health Questionnaire-2 and anxiety using the Generalized Anxiety Disorder-2 scale in student-athletes attending elite sport high schools in Sweden during the second wave of the pandemic (February 2021; n = 7021) and after all restrictions were lifted (February 2022; n = 6228). Depression among student-athletes decreased from 19.8% in 2021 to 17.8% in 2022 (p = .008, V = .026), while anxiety screening did not change significantly (17.4% to 18.4%, p > .05). Comparisons between classes across years revealed older students exhibited decreases in depressive symptoms, while younger cohorts experienced increases in symptoms of anxiety from 2021 to 2022. Logistic regressions revealed that being female, reporting poorer mental health due to COVID-19, and excessive worry over one`s career in sports were significant predictors of both depression and anxiety screenings in 2022. Compared to times when sports participation was limited, the lifting of restrictions was associated with overall reduced levels of depression, but not anxiety.